2020
DOI: 10.3390/mi11090811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blade Outlet Angle on the Flow Field and Preventing Overload in a Centrifugal Pump

Abstract: The influence of the blade outlet angle on preventing overload in a submersible centrifugal pump and the pump performance characteristics were studied numerically for a low specific speed multi-stage submersible pump. The tested blade outlet angles were 16°, 20°, 24°, 28°, and 32°. The results show that the blade outlet angle significantly affects the external flow characteristics and the power curve can be controlled to prevent overload by properly reducing the blade outlet angle. Increasing the blade outlet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Tao et al [22] studied the influence of blade leading-edge shape on the cavitation and concluded it delayed the inception cavitation and critical cavitation. Peng et al [23] analyzed various blade outlet angles without changing other impeller parameters and concluded that if the blade outlet angle was increased, the flow separation and the axial vortex along the blade working surface would be more serious. However, their work was aimed at low specific speed submersible pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al [22] studied the influence of blade leading-edge shape on the cavitation and concluded it delayed the inception cavitation and critical cavitation. Peng et al [23] analyzed various blade outlet angles without changing other impeller parameters and concluded that if the blade outlet angle was increased, the flow separation and the axial vortex along the blade working surface would be more serious. However, their work was aimed at low specific speed submersible pumps.…”
Section: Introductionmentioning
confidence: 99%
“…The force increased as the outlet blade angle increased under constant flow rate conditions. Peng et al (2020) discussed the influence of the outlet blade angle in preventing overload in a centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [22] found that with an increase in the blade rotation angle, the best efficiency point shifts toward a large flow condition under the pump mode and turbine mode; the authors also analyzed the evolution of the tip leakage vortex when the blade rotation angles are 4°and −4°. Peng et al [23] showed that increasing the blade outlet angle pair reduces the cavitation performance of a multistage submersible pump with a low specific speed and increase the flow separation of the blade working surface. Feng et al [24] set up a mathematical model based on the basis of the minimum daily operating cost of a pump station and summarized the influence of adjusting the blade angle frequency on the optimal operation of the pump station; they proposed to adjust the blade angles four to six times a day.…”
Section: Introductionmentioning
confidence: 99%